Turbulence regulation with radial wavenumber spectral shift caused by externally driven E × B velocity shear during edge-localized mode mitigation. (14th October 2019) - Xiao, G.L.; Zou, X.L.; Zhong, W.L.; Song, S.D.; Duan, X.R.; Liu, A.D.; Bai, X.Y.; Cheng, J.; Cui, Z.Y.; Delpech, L.; Ding, X.T.; Dong, J.Q.; et al.
Abstract: Mitigation of edge-localized modes by lower hybrid current drive (LHCD) has been observed in H-mode plasmas of the HL-2A tokamak. It has been found that this mitigation is strongly desynchronized with the LHCD pulse but synchronized with the pedestal turbulence enhancement. This turbulence is enhanced by LHCD induced pedestal velocity shear resulting from the ion diamagnetic term . This velocity shear modifies the turbulence radial wavenumber ( k r ) spectrum by varying the averaged radial wavenumber from large negative value to zero, reducing the turbulence dissipation . A modified turbulence spectral shift model has been used to simulate the experimental results. A critical growth rate for the turbulence regulation is identified in this model and experimentally determined. The criterion for triggering the spectral shift and turbulence enhancement is established. It has been found that there exists a threshold U c of the LHCD induced velocity shear rate, which determines the desynchronization time delay. This threshold value is directly related to, for the pedestal turbulence enhancement. Good agreement has been found between experiment and theory for the regulation of the turbulence intensity calculated with a selected poloidal wavenumber by its averaged radial wavenumber.